Assessment of the Private Health Sector in the Republic of Congo - Makinen, Marty; Deville, Leo; Folsom, Amanda (Washington, DC: World Bank, 2012)
The private health sector was officially recognized in the Republic of Congo over 20 years ago June 6, 1988, establishing the conditions for the independent practice of medicine and the medical-related and pharmaceutical professions. The Congolese government recently expressed its commitment to working with the private health sector in order to strengthen the health system, improve the health of the population and preserve the basic human right to a healthy life through the National Health Care Policy, which it adopted in 2003, the 2007-2011 National Health Development Plan and the 2010 Health Care Services Development Program. Throughout these various documents there is an acknowledgement that the lack of coordination with the private health sector is a weakness of the health system. Nevertheless, the scarcity of information about the private sector in policy and planning documents suggests that the government's engagement with the private health sector is limited. There is no official government policy on the private health sector, or strategies or working plans to encourage cooperation between the public and private sectors. The objective of this assessment was to better determine the role, position, and importance of the private sector within the health system, in order to identify the limitations to its development as well as ways it can be integrated into the efforts to meet the objectives of the Plan national de developpement sanitaire (PNDS) [National Health Development Plan]. The World Bank Group contracted with the Results for Development Institute (R4D, United States) and Health Research for Action (HERA, Belgium) as well as with a team of local consultants, to conduct a 'study of the private health sector in the Republic of Congo.' This study was conducted in close collaboration with the Ministry of Health and Population (MSP), which arranged and oversaw a steering committee consisting of actors from the public and private sectors to facilitate and guide the study. The goal of the study and the workshops was a concrete plan of action for the health sector that could be used by the Congolese government, the private sector in the Republic of Congo, and international development partners. Certain aspects of the action plan should be included in the work programs of the Programme de developpement des services de sante (PDSS) [Health System Development Project] for the years 2011-2013.